Resilience and Self-esteem of Broken Home Teenagers - Silviedriya Mayfani; Anne Hafina Adiwinata; Nadia Aulia Nadhirah (Ma'soem University, 2022)
Family is an important factor in shaping a child's personality. If a family experiences problems such as a broken home, this will have an impact on the psychological development and behavior of the child. The disharmony that occurs in the family experienced by parents certainly has a big impact on the child's life in the future. The impact of this disharmony will be increasingly felt when the child has entered the stage of adolescent development. This is because, at the adolescent stage, children experience development both cognitively and emotionally. To reduce the impact of a broken home situation, adolescents need resilience as a system of resilience from an unstable state (broken home) to rise mentally and personally stronger. Resilience is needed for teenagers who have a broken home family background to be able to get out of stressful situations. One of the factors that can form resilience is self-esteem. The purpose of this study was to determine the relationship between self-esteem and resilience in adolescents who come from broken home families. In this study, the research method used was literature study, and the data collection technique used was qualitative research techniques by describing the problems studied and investigated. The data analysis used is the content analysis technique. The results of this study are that there is a very significant positive relationship between selfesteem and resilience in adolescents with broken home family backgrounds by presenting reading resources based on the theory and results of previous research.Keywords: resilience, self-esteem, adolescence , broken home